Preparation method of aluminum silicate-based nanoflower porous material

Through hydrothermal reaction and calcination treatment, aluminum silicate nanoflowers with fibrous open pores were prepared, which solved the problems of small specific surface area and insufficient pore structure in the prior art, and improved the catalytic reaction efficiency.

CN119430209AActive Publication Date: 2025-02-14HUNAN UNIV OF SCI & TECH

Patent Information

Application Number
CN202411828515.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-14
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing aluminum silicate preparation methods are not suitable in certain special fields, such as small specific surface area, insufficient pore structure types and difficulty in forming nanoflowers with open fiber pores.

Method used

Water-soluble aluminum salt, benzoic acid and polyvinylpyrrolidone dissolved in a specific solvent for hydrothermal reaction, obtain biconical organometallic nanoparticles, and form aluminum silicate nanoflowers with fibrous open pores through calcination and hydrothermal reaction. .

Benefits of technology

The prepared aluminum silicate nanoflowers have a large specific surface area and a special nanoflower-like morphology. They are suitable for catalytic reactions and improve the catalytic reaction efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430209A_ABST
    Figure CN119430209A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an aluminum silicate-based nanoflower porous material, the prepared product presents a special nanoflower-shaped morphology, has fibrous open pore channels, and has the characteristics of highly open space, effective utilization of active sites and the like, aluminum salt, TEOS (tetraethyl orthosilicate) and the like are adopted as raw materials, and the aluminum silicate-based nanoflower porous material is prepared. A novel catalyst carrier material with a nano flower-shaped structure is prepared by a hydrothermal method. Due to the large pore volume between the nano petals and an excellent directly reachable interface structure, various catalytic active sites can be well dispersed on the surfaces of the petal structures. The preparation process is simple and controllable, and the obtained product is rich in hole pattern, high in specific surface area and convenient for industrial preparation. Meanwhile, the obtained product is convenient for further processing and preparation of a catalyst with extremely excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation and porous material preparation, and in particular relates to a method for preparing an aluminum silicate-based nanoflower porous material. Background Art

[0002] Aluminum silicate is an important inorganic material with multiple uses. Due to its unique physical and chemical properties, this material not only has a wide range of uses, but also occupies an important position in modern industry. Aluminum silicate usually appears as colorless crystals or white to gray powders, and it is insoluble in water. Aluminum silicate has low thermal conductivity, excellent thermal stability and good chemical stability, which makes it very important in coatings and paints, papermaking industry, refractory materials and catalyst carrier materials. However, with the change of times and the rapid development of science and technology, traditional aluminum silicate materials have certain limitations in industrial applications, especially some special requirements for material specific surface area and pore size, such as in the field of VOCs control. In order to meet the special needs of these fields, aluminum silicate nanoflowers with large pore volume and excellent directly accessible interface structure have emerged.

[0003] Aluminum silicate nanoflowers are made of aluminum salts and TEOS through a hydrothermal method. Due to their special interface structure, the surface of the petal structure of aluminum silicate nanoflowers can well disperse various catalytic active sites.

[0004] Existing methods for preparing aluminum silicate include: preparing amorphous aluminum silicate by co-precipitation, preparing aluminum silicate carrier by fractional precipitation, and preparing nano aluminum silicate by chemical precipitation or microwave drying. However, the products obtained by these methods are not applicable in certain special fields, that is, the specific surface area is too small, the types of pore structures are insufficient, and it is difficult to form nanoflowers with fiber open pores, etc. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing an aluminum silicate-based nanoflower porous material. The prepared product of the present invention exhibits a special nanoflower-like morphology, has fibrous open pores, has highly open space and effective utilization of active sites, etc. The aluminum silicate nanoflower of the present invention presents a special nanoflower-like morphology, has fibrous open pores, has highly open space and effective utilization of active sites, and the like.

[0006] The present invention provides a method for preparing an aluminum silicate-based nanoflower porous material, comprising the following steps: Step 1: water-soluble aluminum salt, benzoic acid, and polyvinyl pyrrolidone are dissolved in solvent A, and then a hydrothermal reaction is carried out. The obtained precipitate is washed and dried to obtain aluminum-containing bipyramidal organic metal nanoparticles; the solvent A is composed of ethanol, acetone, nitric acid, and water; Step 2: placing the product obtained in step 1 into a tube furnace for calcination, and obtaining an aluminum-containing organic metal framework after calcination; Step 3: Add the product obtained in step 2 and urea to solvent B and mix them evenly, then add organic silicate and carry out hydrothermal reaction; the obtained product is washed, dried and calcined to obtain aluminum silicate nanoflowers; the solvent B consists of methanol and water.

[0007] The preparation method of the invention is simple and easy to implement, and the conditions are mild.

[0008] In step 1 of the present invention, the water-soluble aluminum salt is selected from at least one of aluminum nitrate, aluminum sulfate, and aluminum silicate, preferably aluminum nitrate. When used in industry, a hydrate of aluminum nitrate, such as aluminum nitrate nonahydrate, can be selected.

[0009] In step 1 of the present invention, the benzoic acid is selected from at least one of trimesic acid, p-benzoic acid, o-benzoic acid, and iso-benzoic acid, preferably trimesic acid.

[0010] As a preferred solution, aluminum nitrate nonahydrate, trimesic acid, and polyvinyl pyrrolidone are dissolved in solvent A, and then subjected to a hydrothermal reaction, and the precipitate is washed three times with ethanol and centrifuged and dried. Furthermore, in step 1, the mass ratio of trimesic acid, aluminum nitrate nonahydrate, and polyvinyl pyrrolidone is 1:2~4:6~8, and the volume ratio of nitric acid, water, ethanol, and acetone with a volume concentration of 32.5% is 1:2~4:7~9:7~9.

[0011] Furthermore, in step 1, the mass ratio of trimesic acid, aluminum nitrate nonahydrate and polyvinyl pyrrolidone is 1:2.5~3.5:6~7.0.

[0012] Furthermore, in step 1, the volume ratio of nitric acid with a volume concentration of 32.5%, water, ethanol and acetone is: 1:2.5~3.5:7~8:7~8.

[0013] Furthermore, the hydrothermal reaction temperature in step 1 is 140-160°C and the reaction time is 40-50 hours. Too high or too low a temperature will result in the failure to form bipyramidal nanoparticles after step 1, and further the failure to form expanded aluminum silicate nanoflowers after step 3.

[0014] Furthermore, the drying temperature in step 1 is 90-100°C.

[0015] Furthermore, the temperature of the calcination treatment in the tubular furnace in step 2 is 440-550°C, preferably 475-525°C, and the time is 1-2 hours. Too high a temperature will lead to the formation of compact Al2O3, which will affect the subsequent expansion of aluminum silicate nanoflowers. Too low a temperature will lead to the formation of a transitional pore structure, which will also fail to expand to form aluminum silicate nanoflowers.

[0016] Furthermore, in step 3, urea is added to solvent B, wherein the mass ratio of urea to solvent B is 1:200-300, preferably 1:200-220. Without adding urea, fully expanded aluminum silicate nanoflowers cannot be formed after performing all the steps.

[0017] Furthermore, in step 3, the organic silicate is selected from at least one of tetraethyl orthosilicate, methyl silicate, phenyl silicate, and silane coupling agent. The mass ratio of the organic silicate to the solvent B is 1:8-12. When the content of the organic silicate is too high, silicon balls are easily formed after all steps are performed, which hinders the expansion of the aluminum silicate nanoflowers; when the content of the silicate is too low, complete aluminum silicate nanoflowers cannot be formed after all steps are performed.

[0018] Furthermore, the hydrothermal reaction temperature in step 3 is 160-220°C, preferably 185-205°C, and the reaction time is 14-16 h. In industrial applications, after the hydrothermal reaction is completed, the obtained product aluminum silicate nanoflowers are washed with ethanol at least twice and dried. The drying method includes centrifugal drying.

[0019] In step 3, the calcination temperature is 525-575° C., the calcination time is 30-12 min, preferably 45-90 min, and the calcination atmosphere is an oxygen-containing atmosphere, preferably an air atmosphere.

[0020] The advantages and positive effects of the present invention are: 1. The aluminum silicate nanoflowers of the present invention present a special nanoflower-like morphology and have fibrous open pores, which promote the dispersion of active metal species components and improve the catalytic reaction efficiency in the hydrogenation of carbon dioxide to methanol.

[0021] 2. The present invention obtains aluminum silicate nanoflowers with large specific surface area, nanoflower-like morphology and fibrous open pores through the synergistic effect of process, temperature, material ratio and reaction time. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the scanning electron microscope image of sample 1; Figure 2 is the scanning electron microscope image of sample 2; Figure 3 is the scanning electron microscope image of sample 3; Figure 4is the scanning electron microscope image of sample 4; Figure 5 is the scanning electron microscope image of sample 5; Figure 6 is the scanning electron microscope image of sample 6; Figure 7 is the scanning electron microscope image of sample 7; Figure 8 is the scanning electron microscope image of sample 8; Fig. 9 is the scanning electron microscope image of sample 9; Fig.10 is the scanning electron microscope image of sample 10; Fig.11 is the scanning electron microscope image of sample 11; Fig.12 is a scanning electron microscope image of sample 12; Fig.13 is the scanning electron microscope image of sample 13; Fig.14 is a scanning electron microscope image of sample 14; Fig.15 is the scanning electron microscope image of sample 15; Fig.16 is a scanning electron microscope image of sample 16; Fig.17 is the scanning electron microscope image of sample 17; Fig.18 is a scanning electron microscope image of sample 18; Fig.19 is the scanning electron microscope image of sample 19; Fig. 20 is a scanning electron microscope image of sample 20; Fig.21 is the scanning electron microscope image of sample 21; Fig. 22 This is the scanning electron microscope image of sample 22. DETAILED DESCRIPTION

[0023] The present invention is described in detail below in conjunction with specific embodiments, but is by no means intended to limit the present invention. Features such as preparation methods, materials, structures or composition ratios not explicitly described in this technical solution are considered to be common technical features disclosed in the prior art.

[0024] The following examples will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several modifications and improvements may be made without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.

[0025] The practice of the present invention may employ conventional techniques of polymer chemistry within the skill of the art. In the following examples, efforts have been made to ensure accuracy with respect to numbers used (including amounts, temperatures, reaction times, etc.), but some experimental errors and deviations should be accounted for.

[0026] In this embodiment, all reagents used are commercially available reagents.

[0027] Embodiment 1: This embodiment provides a method for preparing aluminum silicate nanoflowers, comprising the following steps: Step 1: 2875 mg of aluminum nitrate nonahydrate, 1000 mg of trimesic acid, and 6375 mg of polyvinyl pyrrolidone were dissolved in a mixture of 93.75 mL of ethanol, 93.75 mL of acetone, 12.5 mL of nitric acid with a volume concentration of 32.5%, and 37.5 mL of water, and the mixture was fully ultrasonically dispersed. The mixture was transferred to a Teflon-lined reactor and hydrothermally reacted and precipitated at 150°C for 45 hours to obtain a relatively dense precipitate. The precipitate was washed three times with ethanol and centrifuged and dried at a temperature of 95°C. The dried product was observed to be bipyramidal solid nanoparticles (such as Figure 1 As shown), recorded as sample 1; Step 2: 40 mg of bipyramidal nanoparticles were placed in a tube furnace and calcined at 500°C in air atmosphere at a heating rate of 1°C / min for 1 h to obtain active transition state alumina. The bipyramidal hollow nanoparticles (such as Figure 2 As shown), recorded as sample 2; Step 3: The active transition alumina prepared in step 2 and 120 mg of urea were ultrasonically dispersed in a mixture of 20 mL of methanol and 10 mL of deionized water, and a mixed solution of tetraethyl orthosilicate and methanol in a mixing ratio of 1:10 was added and fully ultrasonically dispersed. The mixture was transferred to a 190°C autoclave for hydrothermal reaction for 15 h, and the precipitate was washed three times with ethanol and centrifuged to dry. The dried product was then placed in a tubular furnace and calcined at 550°C in an air atmosphere at a heating rate of 1°C / min for 1 h. At this time, relatively pure aluminum silicate nanoflower particles (such as Figure 3 as shown), recorded as sample 3.

[0028] Embodiment 2: This embodiment provides a method for preparing aluminum silicate nanoflowers, comprising the following steps: Step 1: 2875 mg of aluminum nitrate nonahydrate, 1000 mg of trimesic acid, and 6375 mg of polyvinyl pyrrolidone were dissolved in a mixture of 93.75 mL of ethanol, 93.75 mL of acetone, 12.5 mL of nitric acid with a volume concentration of 32.5%, and 37.5 mL of water, and the mixture was fully ultrasonically dispersed. The mixture was transferred to a Teflon-lined reactor and hydrothermally reacted and precipitated at 150°C for 45 hours to obtain a relatively dense precipitate. The precipitate was washed three times with ethanol and centrifuged and dried at a temperature of 95°C. The dried product was observed to be bipyramidal solid nanoparticles (such as Figure 1 As shown), recorded as sample 1; Step 2: 40 mg of bipyramidal nanoparticles were placed in a tube furnace and calcined at 450°C in an air atmosphere at a heating rate of 1°C / min for 1 h to obtain active transition state alumina. The bipyramidal hollow nanoparticles (such as Figure 4 As shown), recorded as sample 4; Step 3: The active transition alumina prepared in step 2 and 120 mg of urea were ultrasonically dispersed in a mixture of 20 mL of methanol and 10 mL of deionized water, and a mixed solution of tetraethyl orthosilicate and methanol in a mixing ratio of 1:10 was added and fully ultrasonically dispersed. The mixture was transferred to a 190°C autoclave for hydrothermal reaction for 15 h, and the precipitate was washed three times with ethanol and centrifuged to dry. The dried product was then placed in a tubular furnace and calcined at 550°C in an air atmosphere at a heating rate of 1°C / min for 1 h. At this time, relatively pure aluminum silicate nanoflower particles (such as Figure 5 as shown), recorded as sample 5.

[0029] Embodiment 3: This embodiment provides a method for preparing aluminum silicate nanoflowers, comprising the following steps: Step 1: 2875 mg of aluminum nitrate nonahydrate, 1000 mg of trimesic acid, and 6375 mg of polyvinyl pyrrolidone were dissolved in a mixture of 93.75 mL of ethanol, 93.75 mL of acetone, 12.5 mL of nitric acid with a volume concentration of 32.5%, and 37.5 mL of water, and the mixture was fully ultrasonically dispersed. The mixture was transferred to a Teflon-lined reactor and hydrothermally reacted and precipitated at 150°C for 45 hours to obtain a relatively dense precipitate. The precipitate was washed three times with ethanol and centrifuged and dried at a temperature of 95°C. The dried product was observed to be bipyramidal solid nanoparticles (such as Figure 1 As shown), recorded as sample 1; Step 2: 40 mg of bipyramidal nanoparticles were placed in a tube furnace and calcined at 500°C in air atmosphere at a heating rate of 1°C / min for 1 h to obtain active transition state alumina. The bipyramidal hollow nanoparticles (such as Figure 2 As shown), recorded as sample 2; Step 3: The active transition alumina prepared in step 2 and 120 mg of urea were ultrasonically dispersed in a mixture of 20 mL of methanol and 10 mL of deionized water, and a mixed solution of tetraethyl orthosilicate and methanol in a mixing ratio of 1:8 was added and fully ultrasonically dispersed. The mixture was transferred to a 190°C autoclave for hydrothermal reaction for 15 h, and the precipitate was washed three times with ethanol and centrifuged to dry. The dried product was then placed in a tubular furnace and calcined at 550°C in an air atmosphere at a heating rate of 1°C / min for 1 h. At this time, relatively pure aluminum silicate nanoflower particles (such as Figure 6 as shown), recorded as sample 6.

[0030] Embodiment 4: This embodiment provides a method for preparing aluminum silicate nanoflowers, comprising the following steps: Step 1: 2875 mg of aluminum nitrate nonahydrate, 1000 mg of trimesic acid, and 6375 mg of polyvinyl pyrrolidone were dissolved in a mixture of 93.75 mL of ethanol, 93.75 mL of acetone, 12.5 mL of nitric acid with a volume concentration of 32.5%, and 37.5 mL of water, and the mixture was fully ultrasonically dispersed. The mixture was transferred to a Teflon-lined reactor and hydrothermally reacted and precipitated at 150°C for 45 hours to obtain a relatively dense precipitate. The precipitate was washed three times with ethanol and centrifuged and dried at a temperature of 95°C. The dried product was observed to be bipyramidal solid nanoparticles (such as Figure 1 As shown), recorded as sample 1; Step 2: 40 mg of bipyramidal nanoparticles were placed in a tube furnace and calcined at 500°C in air atmosphere at a heating rate of 1°C / min for 1 h to obtain active transition state alumina. The bipyramidal hollow nanoparticles (such as Figure 2 As shown), recorded as sample 2; Step 3: The active transition alumina prepared in step 2 and 120 mg of urea were ultrasonically dispersed in a mixture of 20 mL of methanol and 10 mL of deionized water, and a mixed solution of tetraethyl orthosilicate and methanol in a mixing ratio of 1:12 was added and fully ultrasonically dispersed. The mixture was transferred to a 190°C autoclave for hydrothermal reaction for 15 h, and the precipitate was washed three times with ethanol and centrifuged to dry. The dried product was then placed in a tubular furnace and calcined at 550°C in an air atmosphere at a heating rate of 1°C / min for 1 h. At this time, relatively pure aluminum silicate nanoflower particles (such as Figure 7 as shown), recorded as sample 7.

[0031] Embodiment 5: This embodiment provides a method for preparing aluminum silicate nanoflowers, comprising the following steps: Step 1: 2875 mg of aluminum nitrate nonahydrate, 1000 mg of trimesic acid, and 6375 mg of polyvinyl pyrrolidone were dissolved in a mixture of 93.75 mL of ethanol, 93.75 mL of acetone, 12.5 mL of nitric acid with a volume concentration of 32.5%, and 37.5 mL of water, and the mixture was fully ultrasonically dispersed. The mixture was transferred to a Teflon-lined reactor and hydrothermally reacted and precipitated at 150°C for 45 hours to obtain a relatively dense precipitate. The precipitate was washed three times with ethanol and centrifuged and dried at a temperature of 95°C. The dried product was observed to be bipyramidal solid nanoparticles (such as Figure 1 As shown), recorded as sample 1; Step 2: 40 mg of bipyramidal nanoparticles were placed in a tube furnace and calcined at 500°C in air atmosphere at a heating rate of 1°C / min for 1 h to obtain active transition state alumina. The bipyramidal hollow nanoparticles (such as Figure 2 As shown), recorded as sample 2; Step 3: The active transition alumina prepared in step 2 and 120 mg of urea were ultrasonically dispersed in a mixture of 20 mL of methanol and 10 mL of deionized water, and a mixed solution of tetraethyl orthosilicate and methanol in a mixing ratio of 1:10 was added and fully ultrasonically dispersed. The mixture was transferred to a 175°C autoclave for hydrothermal reaction for 15 h, and the precipitate was washed three times with ethanol and centrifuged to dry. The dried product was then placed in a tubular furnace and calcined at 550°C in an air atmosphere at a heating rate of 1°C / min for 1 h. At this time, relatively pure aluminum silicate nanoflower particles (such as Figure 8 as shown), recorded as sample 8.

[0032] Embodiment 6: This embodiment provides a method for preparing aluminum silicate nanoflowers, comprising the following steps: Step 1: 2875 mg of aluminum nitrate nonahydrate, 1000 mg of trimesic acid, and 6375 mg of polyvinyl pyrrolidone were dissolved in a mixture of 93.75 mL of ethanol, 93.75 mL of acetone, 12.5 mL of nitric acid with a volume concentration of 32.5%, and 37.5 mL of water, and the mixture was fully ultrasonically dispersed. The mixture was transferred to a Teflon-lined reactor and hydrothermally reacted and precipitated at 150°C for 45 hours to obtain a relatively dense precipitate. The precipitate was washed three times with ethanol and centrifuged and dried at a temperature of 95°C. The dried product was observed to be bipyramidal solid nanoparticles (such as Figure 1 As shown), recorded as sample 1; Step 2: 40 mg of bipyramidal nanoparticles were placed in a tube furnace and calcined at 500°C in air atmosphere at a heating rate of 1°C / min for 1 h to obtain active transition state alumina. The bipyramidal hollow nanoparticles (such as Figure 2 As shown), recorded as sample 2; Step 3: The active transition alumina prepared in step 2 and 120 mg of urea were ultrasonically dispersed in a mixture of 20 mL of methanol and 10 mL of deionized water, and a mixed solution of tetraethyl orthosilicate and methanol in a mixing ratio of 1:10 was added and fully ultrasonically dispersed. The mixture was transferred to a 200°C autoclave for hydrothermal reaction for 15 h, and the precipitate was washed three times with ethanol and centrifuged to dry. The dried product was then placed in a tubular furnace and calcined at 550°C in an air atmosphere at a heating rate of 1°C / min for 1 h. At this time, relatively pure aluminum silicate nanoflower particles (such as Fig. 9 as shown), recorded as sample 9.

[0033] Comparative Example 1: In this comparative example, the temperature of the Teflon-lined reactor in step 1 is adjusted to 75°C. The difference from Example 1 is that the temperature of the Teflon-lined reactor in step 1 is too low. The other steps and conditions remain unchanged. The product after completing step 1 is recorded as sample 10. Fig.10 , the product after completing step 3 is recorded as sample 11, such as Fig.11 .

[0034] like Figure 4 The shape of sample 10 prepared in this comparative example observed under a scanning electron microscope is long and narrow or aggregated, which is inconsistent with the shape of sample 1; the product of sample 11 prepared in this comparative example observed under a scanning electron microscope does not unfold into a flower and does not form obvious petals.

[0035] The results show that when the temperature in the Teflon-lined reactor in step 1 is too low, biconical nanoparticles cannot be formed after step 1 is executed, and aluminum silicate nanoflowers cannot be formed after step 3 is executed. Therefore, aluminum silicate nanoparticles cannot be produced when the temperature is too low.

[0036] Comparative Example 2: In this comparative example, the temperature of the Teflon-lined reactor in step 1 is adjusted to 225°C. The difference from Example 1 is that the temperature of the Teflon-lined reactor in step 1 is too high. The other steps and conditions remain unchanged. The product after completing step 1 is recorded as sample 12. Fig.12 , the product after completing step 3 is recorded as sample 13, such as Fig.13 .

[0037] like Fig.12 The shape of sample 12 prepared in this comparative example observed under a scanning electron microscope is long and strip-shaped or aggregated, which is inconsistent with the shape of sample 1; the product of sample 13 prepared in this comparative example observed under a scanning electron microscope does not unfold into a flower and does not form obvious petals.

[0038] The results show that when the temperature in the Teflon-lined reactor in step 1 is too high, biconical nanoparticles cannot be formed after step 1 is executed, and aluminum silicate nanoflowers cannot be formed after step 3 is executed. Therefore, aluminum silicate nanoflowers cannot be produced when the temperature is too high.

[0039] Comparative Example 3: In this comparative example, the calcination temperature is adjusted to 400°C in step 2, and the heating rate remains unchanged. The difference from Example 1 is that the calcination temperature in step 2 is adjusted too low, and the other steps and conditions remain unchanged. The product prepared after executing step 2 is recorded as sample 14. Fig.14 The product prepared after executing step 3 is recorded as sample 15. Fig.15 .

[0040] like Figure 8 As shown, the transparency of the nanoparticles of sample 14 prepared in this comparative example observed under a scanning electron microscope is not as good as that of sample 2, proving that active transition state alumina has not yet been prepared. The petals formed by the product of sample 15 prepared in this comparative example observed under a scanning electron microscope are not fully unfolded.

[0041] The results show that when the calcination temperature in step 2 is too low, active transition alumina cannot be formed after step 2 is completed, and acid aluminum nanoflowers cannot be formed after step 3 is completed. Therefore, when the temperature is too low, aluminum silicate nanoflowers cannot be produced.

[0042] Comparative Example 4: In this comparative example, the calcination temperature is adjusted to 750°C in step 2, and the heating rate remains unchanged. The difference from Example 1 is that the calcination temperature in step 2 is adjusted too high, and the other steps and conditions remain unchanged. The product prepared after executing step 2 is recorded as sample 16. Fig.16 The product prepared after executing step 3 is recorded as sample 17. Fig.17 .

[0043] like Fig.10 As shown, the nanoparticles of sample 16 prepared in this comparative example observed under a scanning electron microscope formed compact Al2O3, proving that active transition alumina has not been prepared. The petals of the product of sample 17 prepared in this comparative example observed under a scanning electron microscope were not fully unfolded.

[0044] The results show that when the calcination temperature in step 2 is too high, active transition alumina cannot be formed after step 2 is executed, and acid aluminum nanoflowers cannot be formed after step 3 is executed. Therefore, when the temperature is too high, aluminum silicate nanoflowers cannot be produced.

[0045] Comparative Example 5: In this comparative example, urea is not added in step 3. The difference from Example 1 is that urea is not added in step 3, and other steps and conditions remain unchanged. The product prepared after executing step 3 is recorded as sample 18. Fig.18 .

[0046] like Fig.18 As shown, no fully expanded aluminum silicate nanoflowers were observed in sample 18 prepared in this comparative example under a scanning electron microscope.

[0047] The results showed that when urea was not added in step 3, fully expanded aluminum silicate nanoflowers could not be formed after all the steps were completed, proving that urea was an indispensable factor in the preparation of aluminum silicate nanoflowers.

[0048] Comparative Example 6: In this comparative example, a mixed solution of tetraethyl orthosilicate and methanol in a mixing ratio of 1:1 is added in step 3 and fully ultrasonically dispersed. The difference from Example 1 is that the content of tetraethyl orthosilicate in step 3 is increased, that is, the content of silicon in the mixed solution is increased, and other conditions and steps remain unchanged. The product prepared after executing step 3 is recorded as sample 19. Fig.19 .

[0049] like Fig.19 As shown, in sample 19 prepared in this comparative example, no aluminum silicate nanoflowers were observed under an electron microscope, but many silicon spheres were formed instead.

[0050] The results show that when the content of tetraethyl orthosilicate in step 3 is too high, complete aluminum silicate nanoflowers cannot be formed after all steps are completed.

[0051] Comparative Example 7: In this comparative example, a mixed solution of tetraethyl orthosilicate and methanol in a mixing ratio of 1:20 is added in step 3 and fully ultrasonically dispersed. The difference from Example 1 is that the content of tetraethyl orthosilicate in step 3 is reduced, that is, the content of silicon in the mixed solution is reduced, and other conditions and steps remain unchanged. The product prepared after executing step 3 is recorded as sample 20. Fig. 20 .

[0052] like Fig. 20 As shown, the sample 20 prepared in this comparative example was observed to be flaky nanoflowers under a scanning electron microscope, and no formed aluminum silicate nanoflowers appeared.

[0053] The results show that when the content of tetraethyl orthosilicate in step 3 is too low, complete aluminum silicate nanoflowers cannot be formed after all steps are completed.

[0054] Comparative Example 8: In this comparative example, the temperature of the hydrothermal reaction in the autoclave in step 3 is adjusted to 150°C. The difference from Example 1 is that the temperature of the hydrothermal reaction in the autoclave in step 3 is adjusted to a lower temperature, and the other steps and conditions remain unchanged. The product prepared after executing step 3 is recorded as sample 21. Fig.21 .

[0055] like Fig.21 , the sample 21 prepared in this comparative example was observed to have incompletely unfolded nanoflowers under a scanning electron microscope, and no formed nanoflowers appeared.

[0056] The results show that when the temperature of the hydrothermal reaction in the autoclave in step 3 is too low, complete aluminum silicate nanoflowers cannot be formed after all steps are completed, that is, the temperature of the hydrothermal reaction in the autoclave is an important factor affecting the preparation.

[0057] Comparative Example 9: In this comparative example, the temperature of the hydrothermal reaction in the autoclave in step 3 is adjusted to 250°C. The difference from Example 1 is that the temperature of the hydrothermal reaction in the autoclave in step 3 is adjusted to be higher, and the other steps and conditions remain unchanged. The product prepared after executing step 3 is recorded as sample 22. Fig. 22 .

[0058] like Fig. 22 Under a scanning electron microscope, the sample 22 prepared in this comparative example showed over-expanded nanoflowers, whose petals had been destroyed by high temperature and no formed nanoflowers appeared.

[0059] The results show that when the temperature of the hydrothermal reaction in the autoclave in step 3 is too high, complete aluminum silicate nanoflowers cannot be formed after all steps are completed, that is, the temperature of the hydrothermal reaction in the autoclave is an important factor affecting the preparation.

[0060] The specific surface area and pore size distribution of samples 1 to 22 in each embodiment and comparative example were tested and compared using an IW-BK100 specific surface area analyzer (manufactured by Beijing Jingwei Gaobo Science and Technology Co., Ltd.), and the specific surface area and pore size distribution of each sample were investigated. The results are shown in Table 1.

[0061]

[0062] The results show that the aluminum silicate nanoflower preparation process of the invention is authentic and effective, and the accurate and effective preparation method can successfully prepare aluminum silicate nanoflowers, proving that temperature, whether to add urea and the proportion of TEOS are all important influencing factors affecting whether aluminum silicate nanoflowers can be finally prepared.

[0063] In summary, the results show that the aluminum silicate nanoflower preparation process of the invention is real and effective. Comparative Examples 1 to 9 can prove that in the preparation process of aluminum silicate nanoflowers, temperature, whether urea is added, and the proportion of TEOS are all important factors affecting whether aluminum silicate nanoflowers can be finally prepared.

[0064] The above is a description of the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above-mentioned description of the embodiments for the convenience of ordinary technicians in the technical field to understand and use the invention. It is obvious that those familiar with the technology in the field can easily make various modifications to these embodiments and apply the general principles described here to other embodiments without creative work. Therefore, the present invention is not limited to the above-mentioned embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing an aluminum silicate-based nanoflower porous material, characterized in that: Step 1: water-soluble aluminum salt, benzoic acid, and polyvinyl pyrrolidone are dissolved in solvent A, and then a hydrothermal reaction is carried out. The obtained precipitate is washed and dried to obtain aluminum-containing bipyramidal organic metal nanoparticles; the solvent A is composed of ethanol, acetone, nitric acid, and water; Step 2: placing the product obtained in step 1 into a tube furnace for calcination, and obtaining an aluminum-containing organic metal framework after calcination; Step 3: Add the product obtained in step 1 and urea to solvent B and mix them evenly, then add organic silicate and carry out hydrothermal reaction; the obtained product is washed, dried and calcined to obtain aluminum silicate nanoflowers; the solvent B consists of methanol and water.

2. The method for preparing an aluminum silicate-based nanoflower porous material according to claim 1, characterized in that: In step 1, the water-soluble aluminum salt is selected from at least one of aluminum nitrate, aluminum sulfate, aluminum acetate, aluminum oxalate, and aluminum chloride; In step 1, the benzoic acid is selected from at least one of trimesic acid, p-benzoic acid, o-benzoic acid, and isobenzoic acid.

3. The method for preparing an aluminum silicate-based nanoflower porous material according to claim 2, characterized in that: In step 1, the mass ratio of trimesic acid, aluminum nitrate nonahydrate, and polyvinyl pyrrolidone is 1:2-4:6-8, and the volume ratio of nitric acid, water, ethanol, and acetone with a volume concentration of 32.5% is 1:2-4:7-9:7-9.

4. The method for preparing an aluminum silicate-based nanoflower porous material according to claim 1, characterized in that: The hydrothermal reaction temperature in step 1 is 140-160° C. and the reaction time is 40-50 h.

5. The method for preparing an aluminum silicate-based nanoflower porous material according to claim 1, characterized in that: The drying temperature in step 1 is 90-100°C.

6. The method for preparing an aluminum silicate-based nanoflower porous material according to claim 1, characterized in that: In step 2, the calcination is carried out in a tubular furnace, the calcination temperature is 440-550° C., the time is 1-2 hours, and the calcination environment is air.

7. The method for preparing an aluminum silicate-based nanoflower porous material according to claim 1, characterized in that: In step 3, urea is added to solvent B, and the mass ratio of urea to solvent B is 1:200-300.

8. The method for preparing an aluminum silicate-based nanoflower porous material according to claim 1, characterized in that: In step 3, the mass ratio of the organic silicate to the solvent B is 1:8-12.

9. The method for preparing an aluminum silicate-based nanoflower porous material according to claim 1, characterized in that: The hydrothermal reaction in step 3 has a reaction temperature of 160 to 220° C. and a reaction time of 14 to 16 h.

10. The method for preparing an aluminum silicate-based nanoflower porous material according to claim 1, characterized in that: In step 3, the calcination temperature is 525-575° C., the time is 30-12 min, and the calcination atmosphere is an oxygen-containing atmosphere.

Citation Information

Patent Citations

  • Method for preparing hydrated aluminum silicate

    CN101148258A

  • Method for producing tubular aluminum silicate

    JP2016113336A

Cited By

  • Silicon-based nano flower-shaped catalyst composite material as well as preparation method and application thereof

    CN119869534A